Incidence of road traffic disabilities trending upwards in transitional China: a retrospective analysis from 1980 to 2005. Issue 5 (15th May 2014) - Liu, Lan; Du, Wei; Pang, Lihua; Chen, Gong; Zheng, Xiaoying
Abstract : Objective: To evaluate the change in incidence rates of road traffic disabilities from 1980 to 2005 in China. Methods: We employed the 2006 China National Sample Survey on Disability to derive weighted number of persons with disabilities resulting from road crashes and weighted age-gender-specific population at risk by disability occurrence year. The annual incidence rate of road traffic disabilities and corresponding 95% CI were estimated. We used the World Population Prospects (WPP) and the death rate of people with disabilities (PWD) to estimate potential earlier loss of lives before 2006. Both WPP-adjusted and PWD-adjusted incidence rates of road traffic disabilities were further adjusted using the life table analysis. Results: The WPP-adjusted incidence rate for road traffic disabilities increased over time from 1.50 (95% CI 1.47 to 1.52) in 1980 to 11.19 (95% CI 11.13 to 11.25) per 100 000 persons in 2005. The PWD-adjusted incidence rate also increased from 1.71 (95% CI 1.68 to 1.73) to 11.51 (95% CI 11.45 to 11.57) per 100 000 persons. Conclusions: Road crashes disable thousands of Chinese and remain a significant population health and development problem. The increasing burden of road traffic disabilities calls for more efforts and specific strategies to improve road safety in China.